PENGARUH PEMBERDAYAAN KARYAWAN, SELF EFFICACY DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan Produksi CV Jordan Semarang) - Ajeng Tria Jayanti Wulandari; Widiartanto Widiartanto (Universitas Diponegoro, 2019)
Bussiness competition in Indonesia grows very fast and tight both in small and big company. It also occurs in plastic bottle packaging companies in Indonesia.The problem of this research was the degradation of the employee’s performance in production division from 2016 to 2018.This research was aimed to know whether there was influence in employee empowerment, self efficacy and competition towards the performance of the production employee in CV. Jordan. The data collection technique used questionnaire. They were analyzed through validity test, reliability test, determination coefficient, simple linear regression, multiple linear regression, t-test, f-test using SPSS version 23.0 program.The results show that employee empowerment, self efficacy and competition give significant positive influence towards the performance of the employee. Regarding to this research, the company is suggested to improve the employee empowerment, self efficacy and competition so it can improve good performance of the employee.